Type 2 Low Biomarker Stability and Exacerbations in Severe Uncontrolled Asthma - Viinanen Arja; Aakko Juhani; Lassenius Mariann I; Telg Gunilla; Nieminen Kaisa; Kaijala Saara; Lehtimäki Lauri; Kankaanranta Hannu (MDPI, 2025)
We investigated the stability of T2 low status, based on low levels of T2 biomarkers, and exacerbation rates in T2 low and non-T2 low asthma from clinical retrospective data of severe uncontrolled asthma patients. Knowledge of the T2 low biomarker profile is sparse and biomarker stability is uncharted. Secondary care patients with severe uncontrolled asthma and at least two blood eosinophil counts (BEC) and fractional exhaled nitric oxide (FeNO) measured for determination of type 2 inflammation status were evaluated from a follow-up period of 4 years. Patients were stratified into four groups: T2 low(150) (n = 31; BEC < 150 cells/& mu;L and FeNO < 25 ppb), non-T2 low(150) (n = 138; BEC > 150 cells/& mu;L and/or FeNO > 25 ppb), T2 low(300) (n = 66; BEC < 300 cells/& mu;L and FeNO < 25 ppb), and non-T2 low(300) (n = 103; BEC > 300 cells/& mu;L and/or FeNO > 25 ppb). Exacerbation rates requiring hospital care, stability of biomarker status, and cumulative OCS and ICS doses were assessed during follow-up. Among patients with severe uncontrolled asthma, 18% (n = 31) were identified as T2 low(150), and 39% (n = 66) as T2 low(300). In these groups, the low biomarker profile was stable in 55% (n = 11) and 72% (n = 33) of patients with follow-up measures. Exacerbation rates were different between the T2 low and non-T2 low groups: 19.7 [95% CI: 4.3-45.6] in T2 low(150) vs. 8.4 [4.7-13.0] in non-T2 low(150) per 100 patient-years. BEC and FeNO are useful biomarkers in identifying T2 low severe uncontrolled asthma, showing a stable follow-up biomarker profile in up to 72% of patients. Repeated monitoring of these biomarkers is essential in identifying and treating patients with T2 low asthma.